Numerical Simulation of Gas–Liquid Flow Field in PEM Water Electrolyzer - Yusheng Zhang; Xiaoying Yuan; Sheng Yao; Hairui Yang; Cuiping Wang (Energies)
Hydrogen is an excellent clean energy, and hydrogen production by electrolyzing water has become the preferred method. Due to its high electrolysis efficiency and great potential for energy conversion and storage, water electrolysis in a proton exchange membrane (PEM) electrolyzer has attracted considerable attention. In order to explore the factors affecting the internal resistance of PEM water electrolyzers and optimize them, a three-dimensional steady-state model of PEM water electrolyzers coupled with a porous media physical field was established. First, the flow fields in multi-channel and single-channel electrolyzers were designed and comparably simulated. It was found that both flow field configuration and flow modes affected the mass transfer and current distribution. The multi-channel parallel flow field had the lowest flow pressure drop and uniform flow field, which is beneficial to efficient catalytic electrolysis. Secondly, the simulation results of mass transfer in the PEM cell were highly consistent with the reference experimental data, and the increased reference exchange current density (i0) can improve the oxygen/hydrogen production performance of the cell. These findings are helpful in optimizing the design of the PEM water electrolyzer.